Pengetahuan Tentang Manfaat Kesehatan Temulawak (Curcuma xanthorrhiza.) Serta Uji Klinis Pengaruhnya pada Sistem Imun Humoral pada Dewasa Obes - Mira Dewi; Muhammad Aries; . Hardinsyah; Cesilia Meti Dwiriani; Nunuk Januwati (Jurnal Ilmu Pertanian Indonesia, 2012)
Sufficient knowledge of the community regarding benefits of temulawak for health and scientific evidence of its influence on the immune system is crucial for rationalizing the utilization of these plants for health purposes. This study aimed to analyze the public's knowledge about health benefits of temulawak drinks, as well as analyzing the effect of temulawak extract drink consumption on humoral immune system function as assessed by population of B lymphocytes in obese adults. The study consisted of a survey of knowledge about the health benefits of temulawak involving 80 subjects and a clinical trial of the effect of extract temulawak drink consumption given for 2 weeks in 21 obese subjects. Populationof total lymphocytes and B lymphocytes were analyzed before and after intervention. This study showed that the health benefits of temulawak most widely known by subjects were to increase appetite and to maintain stamina. From the clinical trial it was shown that the extract significantly reduce the population of B lymphocytes, indicating a decrease in humoral immune function.